Apparent total tract digestibility and palatability of extruded diets with graded levels of whole soybeans by dogs - Kim, Hee S.; Li, Sang; Zheng, Yi; Aldrich, Charles G. (Frontiers in Veterinary Science, 2023)
however, increasing fat level in dry dog food has been challenging due to the lubrication and limitation of the coating system. The objective was to determine the effect of whole soybeans (WSB) on nutrient digestibility, stool quality, and palatability by dogs. The corn gluten meal, chicken fat, and brewers rice were replaced by WSB at 10%, 20%, and 30% (WSB10, WSB20, and WSB30, respectively) in the base diet (WSB0). Twelve beagles were randomly assigned. The digestibility trial was duplicated 4 × 4 Latin square design where dogs were allowed a 9-d adaptation followed by a 5-d total fecal collection for each period. Least-square means were analyzed with a single degree of freedom contrasts and significance at α = 0.05. Palatability was determined with a 2-bowl test by twenty beagles for 2 d with each WSB diet compared to the WSB0. First choice preference between two diets and total food consumption were recorded. Individual intake ratios (IR) were calculated (intake of each diet/total intake) for each dog. First choice (FC) was analyzed by a Chi-square probability, and the diet consumption was compared by a Wilcoxon signed rank test and a 2-way analysis of variance. Fecal moisture, output, and defecation frequency increased linearly (P < 0.05) as WSB increased. Apparent total tract digestibility of dry matter, organic matter, crude protein, fat, and gross energy decreased linearly (P < 0.05) as dogs fed the increased level of WSB. The fresh fecal pH in dogs decreased linearly (P < 0.05) as WSB content increased. The acetate, propionate, and the total short-chain fatty acid concentration increased linearly (P < 0.05) while the total branched-chain fatty acid concentration decreased linearly (P < 0.05) as WSB increased. Dogs had greater (P < 0.05) FC for WSB diets than WSB0, but there was no difference among treatments for diet consumption and IR. In conclusion, additional thermal processing before extrusion may improve nutrient digestibility of WSB. The stool quality and palatability were not affected, and fermentation in hindgut increased by WSB by dogs.